Evaluating elastic wave velocities in Brazilian municipal solid waste - Aranda C., Nataly M. (2019)
The sanitary landfills in Brazil are, generally, characterized by their high organic material content (around 60%), presence of different types of mixed wastes, and low compaction energy, which differentiates them from the landfills of developed and high-income countries. To prevent environmental and slope stability risks, it is crucial to understand the behavior of such landfills and the changes in their physical properties over time. The compression wave velocity (Vp) and shear wave velocity (Vs) are important parameters to subsidize the mechanical characterization of sanitary landfills, using which can be derived the dynamic elastic properties of municipal solid waste (MSW) for stability analysis. Using the geophysical methods of seismic refraction, active and passive multichannel analysis of surface waves, and crosshole test, it was obtained the values of Vp and Vs by employing an experimental cell and a lysimeter filled with MSW in the City of Campinas, São Paulo State, Brazil. The results obtained from the crosshole test showed that Vp ranged from 217 to 252 m/s and Vs ranged from 86 to 89 m/s. These low values can be attributed to the high content of organic material, low compaction energy, and climatic conditions such as high pluviometry index and high temperatures that together lead to changes in the pore fluid saturation, effective stress, and pore pressure. These values are indicative of the lower limit of the corresponding velocities reported in most literature; however, they are in accordance with the values reported for landfills located in countries with similar socioeconomic and climatic conditions.